Structure-function relationship between plastid morphology and carbon partitioning during secondary cell wall synthesis in Arabidopsis thaliana - Mizrachi, Eshchar (University of Pretoria, 2022)
Dissertation (MSc (Biotechnology))--University of Pretoria, 2022.